Experimentos de campo en economía: preferencias en relación al riesgo y demanda por contratos intertemporales en el Perú - Galarza, Francisco (2010)
This article looks at the determinants of the choice of productive projects involving intertemporal contracts in rural Peru. In a setting where the formal education is limited, the successful launching of new financial instruments may be affected by the lack of proper understanding of their main features, as well as judgment biases. We find that education, a source of judgement bias, and (weakly) risk aversion, affect such a project choice. In contrast, wealth does not appear to play a role in explaining project choice.